Aggressive angiomyxoma of the perineal region. (April 2019) - Raptin, Clémence; Lucot, Jean-Philippe; Bassil, Alfred; Poncelet, Edouard; Prolongeau, Jean-François; Phalippou, Jéröme
Aggressive angiomyxoma is a rare tumour that frequently involves the perineal region with a high risk of local recurrence. This is a case report of a 24-year-old female patient with a genital prolapse. We performed a surgical treatment. Histological examination found an aggressive angiomyxoma. The tumour recurred 1 year after surgery. Long-term follow-up is necessary.